Investigation the Possibilities of Carbon Footprint Reduction of Steam Cracking by Using Hydrocarbons from Wastes - Beatrix Csutoras; Norbert Miskolczi (Chemical Engineering Transactions)
Due to increasing in population and living standards, the demand for plastics has also grown dynamically over the past decades. The light olefins building the polymer chains can be produced in the largest quantities by steam cracking of hydrocarbons. In order to convert hydrocarbons into light olefins with the highest possible conversion, high temperatures and steam are required. Due to the high temperature, steam cracking emits large amounts of greenhouse gases into the atmosphere. In the interests of long-term sustainability and circular economy, the possibilities of CO2 reduction obtained by steam cracking is in the focus. Mainly the suitability of new types of furnaces and heating systems are investigated. Due to the stricter environmental regulations petrochemical industry has to solve significant challenges. This includes the outstanding problem of recycling waste plastics. The aim of our research was to investigate the applicability of liquid hydrocarbons obtained from waste plastics in a steam cracking process. High olefin containing hydrocarbons were produced by low temperature pyrolysis from polymer wastes, then those hydrocarbon fractions were used as feedstock for steam cracking process.